Move structures found in the final project abstracts written by Indonesians and Filipinos - Slamet Utomo; Diah Kurniati; Atik Rokhayani; Ana Espejo Miraña (Universitas Islam Sultan Agung, 2022)
This study was conducted to investigate the move structures of the final project report abstracts produced by the undergraduate students of the English Education Department (EED-UMK) Indonesia and by the Secondary Education undergraduate students of Central Bicol State University of Agriculture (CBSUA) Philippine. This study employed the content analysis method. Sample final project reports from EED-UMK and CBSUA were gathered and analyzed. The findings of this research revealed that the abstracts of EED-UMK and CBSUA used different move structures patterns. The majority of EED-UMK abstracts (80%) referred to Hyland's five move structures, which consisted of introduction, purpose, method, product, and conclusion (I-P-M-Pr-C). Meanwhile, one of the CBSUA abstracts (20%) applied Bathia’s four move structures consisting of purpose, method, result, and conclusion (P-M-R-C). The remaining of the EED UMK and CBSUA abstracts did not address either Bathia's or Hyland's styles. This study concludes that the two Universities have different style structures in writing the final report abstracts. This study suggests that students use the move structure style consistently in their abstracts.